KOMITMEN ORGANISASI DITINJAU DARI TIPE GAYA KEPEMIMPINAN MENURUT LEWIN (Studi Komparatif pada Fungsionaris Lembaga Kemahasiswaan Intra Universitas Negeri Semarang Tahun 2007) (Intuisi : Jurnal Psikologi Ilmiah, 2009)
This Research's purpose is knowing about organization commitment difference between autocratic, democratic, and laissez-faire leadership style on students organization activist in Semarang State University year 2007. The method of research is comparative quantitative. Technique sampling used is proportional stratified random sampling. Instruments of research used are leadership style scale and organizational commitment scale. Technique of analysis used is one way anava. The Result shows there is different organization commitment between autocratic, democratic, and laissez-faire leadership style on student organization activist in Semarang State University year 2007 with coefficient correlation getting Fo 54,664 with significan 0,00. Democratic leadership style has the highest organizational commitment than autocratic and laissez-faire leadership style.